2011
DOI: 10.2494/photopolymer.24.527
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Surface Relief Grating Formation Using Mixed Amorphous Films of Molecular Materials: 4-[4'-Stearoyloxybiphenyl-4-yl(biphenyl-4-yl)-amino]azobenzene-4,4',4''-Tris[3-methylphenyl-(phenyl)amino]triphenylamine System

Abstract: photoinduced SRG formation using a mixed film of DBAB-St and m-MTDATA has been investigated. ExperimentalDBAB-St was synthesized as follows: stearoyl chloride (0.70 g, 2.3 mmol) was added to a THF solution (20 mL) of 4-[4'-hydroxybiphenyl-4-yl(biphenyl-4-yl)amino]azobenzene (DBAB-OH: 1.0 g, 1.9 mmol), prepared by the procedure reported in our previous paper [ 23 ], and triethylamine (0.39 g, 3.9 mmol), and then the solution was stirred for 2 h at room temperature. After the solvent was removed under reduced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The inscription of SRG has also been explored on amorphous low-molecular-weight molecular materials. ,,, Nakano et al compared the gratings formation between several amorphous films composed of azotriarylamine derivatives (Figure u–x), and Ishow et al performed a comparative study of several molecular glasses . There are in addition several examples where the authors proved that their material was in a crystalline phase. , Nakano et al, for instance, observed the formation of SRG at the surface of a single crystal of 4-(dimethylamino)­azobenzene (Figure y).…”
Section: Motion From Photochromic Molecular Switchesmentioning
confidence: 99%
“…The inscription of SRG has also been explored on amorphous low-molecular-weight molecular materials. ,,, Nakano et al compared the gratings formation between several amorphous films composed of azotriarylamine derivatives (Figure u–x), and Ishow et al performed a comparative study of several molecular glasses . There are in addition several examples where the authors proved that their material was in a crystalline phase. , Nakano et al, for instance, observed the formation of SRG at the surface of a single crystal of 4-(dimethylamino)­azobenzene (Figure y).…”
Section: Motion From Photochromic Molecular Switchesmentioning
confidence: 99%